Adopting Mayer’s Design Principles In An Interactive Multimedia Web-Based Learning Module To Promote Student Centered Learning - Yap, Wei Li (INTI International University, 2011)
Many educators are aware that multimedia learning applications can bring positive impact to learners. At the same time, many researchers have claimed teachers and students can enjoy various benefits if multimedia (earning application Is used. However, we have to follow proper design guidelines while designing multimedia applications as not to bring cognitive overload to the students when using them, In this study, Mayer’s design principles (Mayer, 2001) are adopted to design the interactive multimedia web-based learning module. On the other hand, we may also notice that teaching and learning environment has shifted to another paradigm where many universities are introducing student centered learning approach with the aim to achieve better Learning outcomes. This paper would like to share the positive results obtained from the study where students had undergone an Independent learning environment. Pretest and Posttest were given to the students to measure their performance before and after having the lesson using the learning module. Alter the Lesson, students were asked to participate in the survey questionnaires in order to collect the students’ perceptions towards the learning environment and feedback about the Learning module. The results will be interpreted as per the design guidelines recommended by Mayer. This paper concludes with discussion on the positive impacts brought by this teaching and learning approach. With this study, It Intends to share the positive outcomes received and encourages other educators to use this teaching and learning approach.